Performance Development of A BLDC Motor Driven Water Pump Using KY Converter - Anu Priya; Sasilatha Sasilatha (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents a performance investigation of bldc motor employing KY converter. Conventional The landsman converter is  used to minimize the ripples but  the inverter produces high output power ripples, which in turn affect the output of the inverter in The proposed KY converter  reduces ripples and smooth dc supply gives to the inverter  then it will used to operate brushless dc motor, which inturn improves the motor performance. the electronically commutated brushless DC with voltage source inverter can be operated at fundamental frequency is to reduce switching losses which output in higher efficiency.